Ginkgo Biloba aqueous extract attenuated MDMA-induced Neurodegeneration and its accompanying memory aberrations in experimental Wistar rats model - Olanrewaju John Afees; Owolabi Joshua Oladele; Simon Peniel Oluwatoni; Olatunji Sunday Yinka; Enya Joseph Igbo; Arietarhire Leviticus; Adelodun Stephen Taiye; Taiwo-ola Dorcas; Afolabi Toluwanimi; Fabiyi Oluwaseyi Sunday (Elsevier, 2021)
Abstarct: Background: 3,4-methylenedioxymethamphetamine (MDMA) is a psychoactive drug that teenagers and young adults habitually abuse for pleasurable sensations and can cause neurological disorders. Aim: This research focuses on investigating the attenuating potential of Ginkgo biloba (G. biloba) aqueous extract, following MDMA-induced neurodegeneration and its accompanying memory aberrations in rat model. Methods: A total of thirty-two (32) male Wistar rats weighing approximately 140-160 g were randomly divided into four groups, and housed in plastic cages at room temperature. During experimental treatment: CTR-group were given normal saline daily, MDMA-group were given 10mg/kg of MDMA intraperitoneally (ip), G. biloba-group received 200 mg/kg of G. biloba orally and MDMA+ G. biloba-group were given 10 mg/kg of MDMA followed by 200 mg/kg of G. biloba. Substance administration took 22 days. Results: 10 mg/kg ip injection of MDMA obviously reduced body weight and significantly increased the escape time as well as wrong holes poking with depletion in open field test parameters scored. G. biloba was able to ameliorate this. Correspondingly, MDMA treatment reduced the expression of p53, p21, GSH and GPx-1 gene. Disruption in neuronal arrangement, mild depolarization and vacuolation of pyramidial neurons were seen in the histo-architecture. Glial fibrillary acidic protein (GFAP) expression revealed increased astrocyte densities (astrogliosis) in the hippocampus and Ki-67 staining demonstrated the degree of cell proliferation which highly decreased following 10 mg/kg ip injection of MDMA. Conclusion: However, 200 mg/kg of G. biloba aqueous extract was able to restore MDMA-induced hippocampal damage over a period of time, with a need for further investigation to ascertain which phytoconstituent of G. biloba is more effective in the treatment of psychstimulant induced brain damage